A Implementasi Ekonomi Syari'ah : Marketing Syari'ah: MARKETING UANG DIGITAL SYARIAH DAN KONVENSIONAL SEBAGAI SOLUSI EFEKTIF TRANSAKSI BARANG DAN JASA - Sof’an, Mohammad (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2025)
The development of digital technology has driven a major transformation in the payment system, from conventional cash-based methods to the use of electronic or digital money. Digital money, both in conventional and sharia financial systems, offers various advantages such as ease of access, transaction speed, time efficiency, and increasingly guaranteed security. This study aims to examine the use of sharia and conventional digital money in everyday life and analyze the potential and challenges of each system. The research method used is descriptive qualitative through a literature study approach. The results of the discussion show that although the use of digital money is increasing, challenges such as low financial literacy, limited technological infrastructure, and concerns about security and consumer behavior are still obstacles. Specifically in the context of sharia, compliance with Islamic principles such as the prohibition of usury and gharar is an important factor in the adoption of digital financial technology. Conventional banks still dominate the use of cashless transactions due to wider accessibility, although sharia banks such as BSI are starting to show progress. Therefore, the integration between technological efficiency and sharia values ​​is very important in creating an inclusive, fair, and sustainable digital financial system.